2023
DOI: 10.1037/pag0000738
|View full text |Cite
|
Sign up to set email alerts
|

Resilience to stress across the lifespan: Childhood maltreatment, heart rate variability, and bereavement.

Abstract: Following a stressful life event, there is considerable variation in how individuals respond and adapt. Multiple models of risk and resilience show that adverse childhood experiences may be associated with an individual's response to stress later in life. While there is considerable support that early adversity can sensitize the stress response system and lead to adverse outcomes later in life, there is mounting evidence that in adolescence and young adulthood, certain biological predispositions to stress may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 147 publications
0
1
0
Order By: Relevance
“…Previous studies indicate individual differences in how childhood maltreatment may affect an individual's response to bereavement (Chen et al, 2020(Chen et al, , 2023, implying that not all individuals who experience childhood maltreatment experience similar relationship-related thoughts and feelings in adulthood. We found that childhood maltreatment and attachment anxiety can each contribute significantly to predicting depression trajectories beyond the influence of one another.…”
Section: Unique Effects Of Childhood Maltreatment and Attachment Stylementioning
confidence: 99%
“…Previous studies indicate individual differences in how childhood maltreatment may affect an individual's response to bereavement (Chen et al, 2020(Chen et al, , 2023, implying that not all individuals who experience childhood maltreatment experience similar relationship-related thoughts and feelings in adulthood. We found that childhood maltreatment and attachment anxiety can each contribute significantly to predicting depression trajectories beyond the influence of one another.…”
Section: Unique Effects Of Childhood Maltreatment and Attachment Stylementioning
confidence: 99%